2011
DOI: 10.1124/jpet.111.179705
|View full text |Cite
|
Sign up to set email alerts
|

Abuse Liability Profile of Three Substituted Tryptamines

Abstract: The abuse liability profile of three synthetic hallucinogens, N,Ndiisopropyltryptamine (DIPT), 5-N,N-diethyl-5-methoxytryptamine (5-MeO-DET), and 5-methoxy-␣-methyltryptamine (5-MeO-AMT), was tested in rats trained to discriminate hallucinogenic and psychostimulant compounds, including cocaine, methamphetamine, 3,4-methylenedioxymethylamphetamine (MDMA), lysergic acid diethylamide (LSD), (Ϫ)-2,5-dimethoxy-4-methylamphetamine (DOM), and dimethyltryptamine (DMT). Because abused hallucinogens act at 5-hydroxytryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
84
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(91 citation statements)
references
References 25 publications
(32 reference statements)
5
84
0
Order By: Relevance
“…5-MeO-AMT has also been shown to act as a substrate releaser at rat monoamine transporters and the human SERT (Gatch et al, 2011). A recent study showed that 5-MeO-MiPT stimulated 5-HT 2 receptors but did not interact with rat monoamine transporters (Blough et al, 2014), in contrast to its close analog 5-methoxy-diisopropyltryptamine (5-MeO-DiPT), which acted at the SERT (Blough et al, 2014;Sogawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…5-MeO-AMT has also been shown to act as a substrate releaser at rat monoamine transporters and the human SERT (Gatch et al, 2011). A recent study showed that 5-MeO-MiPT stimulated 5-HT 2 receptors but did not interact with rat monoamine transporters (Blough et al, 2014), in contrast to its close analog 5-methoxy-diisopropyltryptamine (5-MeO-DiPT), which acted at the SERT (Blough et al, 2014;Sogawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Different N-substitutions also influenced in vivo potency (Nichols et al, 2015;Repke et al, 1985). The pharmacological profiles of many tryptamines have been studied previously at selected targets (Blough et al, 2014;Gatch et al, 2011;McKenna et al, 1990;Nichols et al, 2015;Repke et al, 1985;Shulgin and Carter, 1980), and new and pharmacologically unknown tryptamine derivatives are constantly emerging on the illicit drug market (Araujo et al, 2015;Corkery et al, 2012;EMCDDA, 2014;Greene, 2013;Helander et al, 2014;Tittarelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations